Active Learning Process in Bidik Misi’s Students of Mathematics Education in Syiah Kuala University - Sry Rasyiidu Tebe; Rahmah Johar; Suhartati Suhartati (Proceedings of AICS - Social Sciences, 2017)
Students’ active learning is a process which isaffected students’ comprehension and ability in term tasks and activities. Consequently, the aim of this study was to dispose the activity of bidik misi’s students of mathematics education in Syiah Kuala University. The population of this study were chosen based on GPA (Grade Point Average) all of bidik misi’s students at mathematics’ education in Syiah Kuala University. The sample was collected by purposive sampling. Purposive sampling was used because there was one class that has the highest number of bidik misi’s students. Besides the students in the force of 2015 has been following several courses so to see the activity that was analyzed based on GPA more efficiently done on that class. Accordingly, ten studentswereselected as sample. Data collection was obtained by observation and interview. The observation was used to identify student’s active learning in class. The interview which was employed to identify the causing of students active learning was done after the observation. In teaching learning process,there were several bidik misi's students is active, howeverthere were several bidik misi's students is not active. it was caused some factors such asstudents’ motivation influenceand students’ environment influence. Keywords: active learning process, learning outcomes, GPA.